Big Data and algorithmic governance: the case of financial practices. Issue 2 (4th March 2017) - Campbell-Verduyn, Malcolm; Goguen, Marcel; Porter, Tony
ABSTRACT: Big Data and algorithmic governance are transforming traditional institutions and media of transnational governance in manners that hold important implications for power, accountability and effectiveness. Drawing on actor-network theory, this paper contrasts utopian or dystopian views on the increasing presence of Big Data in contemporary financial practices. We scrutinise the emerging impacts of Big Data in the public governance of private banks in the Basel III arrangements, private governance of individual actors in credit scoring and anarchic competitive governance of markets in high-frequency trading. Our findings reveal varied and emergent forms of governance through, with and by algorithms.